Targeting CD96 overcomes PD-1 blockade resistance by enhancing CD8+ TIL function in cervical cancer. Issue 3 (14th March 2022) - Wang, Yumeng; Wang, Congwen; Qiu, Junjun; Qu, Xinyu; Peng, Jing; Lu, Chong; Zhang, Meng; Zhang, Mingxing; Qi, Xingling; Li, Guiling; Hua, Keqin
Abstract : Background: Novel therapies are needed to treat recurrent and advanced cervical cancer (CC), as their prognosis remains very poor. Although therapies targeting the programmed cell death protein 1 (PD-1) pathway have been approved for CC, a large subset of patients exhibit innate resistance. Using checkpoint inhibitors in combination could enhance their efficacy. Methods: Blood samples, tumor specimens, and peritumorous (PT) tissues were obtained from patients with CC. The inhibitory receptor expression and phenotypical analysis of CD8+ T cells in CC specimens were analyzed by flow cytometry. The ligands of CD96 expressed by tumor cells were measured by immunohistochemistry and immunofluorescence. Sensitivity to pembrolizumab was evaluated by an ex vivo treatment assay based on the single-cell culture of CC specimens. The efficacies of PD-1 and/or CD96 blockades were explored using an ex vivo treatment assay and an human papillomavirus-positive TC-1 xenograft mouse model in vivo. Results: We found that CD96 expression was elevated on CD8+ tumor-infiltrating lymphocytes (TILs) from patients with CC who were insensitive to the PD-1 blockade. These CD96-expressing CD8+ TILs often coexpressed PD-1. The ratio of the CD96+CD8+/CD96−CD8+ T-cell gene signature from the scRNA-seq data was significantly associated with the poor survival of patients with cervical squamous cell carcinoma and endocervical adenocarcinoma. The costimulatory receptor CD226, which competes with CD96, was downregulated in tumors compared with blood and PT tissue. CD96 and T-cell immunoreceptor with Ig and ITIM domains (TIGIT) were upregulated on intratumoral CD8+ T cells. The CD226/CD96/TIGIT signaling ligands were widely expressed in CC tumor tissues. Phenotypical profiling showed that PD-1+CD96+CD8+ TILs exhibited a terminally exhausted effector phenotype with high levels of T-cell immunoglobulin mucin receptor 3 (TIM-3) and granzyme B (GZMB) and extremely low levels of proinflammatory cytokines and cytotoxic molecules. PD-1+CD96 cells exhibited a precursor exhausted phenotype with TCF-1 positivity. CD96 was further upregulated by CD8+ TILs on PD-1 blockade. Treatment with the CD96 blockade significantly enhanced the PD-1 blockade to blunt tumor growth and improve the function of CD8+ TILs in both mouse and CC specimen models. Conclusions: Our findings showed that CD96 and PD-1 cooperatively and negatively regulate the function of CD8+ TILs, and CD96 blockade has promise for use in combination with PD-1 blockade for the treatment of CC.